2000
DOI: 10.1002/1099-1395(200005)13:5<233::aid-poc235>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanism of decyanation of 2,2-diphenylpropionitrile induced by LiAlH4

Abstract: The LiAlH4 reduction of 2,2‐diphenylpropionitrile (4) in THF yields a mixture of the hydrocarbon 6 and the expected amine 5. Medium effects and reduction with LiAlD4 suggest a mechanism involving the attack of the hydride reagent on the cyano carbon atom followed by the fragmentation of the formed imine salt intermediate. Copyright © 2000 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…An addition–elimination mechanism has been previously proposed for the LiAlH 4 promoted decyanation of 2,2-diphenylpropionitrile and related nitriles. In such pathways, the phenyl groups probably favor the C–C bond cleavage by stabilizing the incipient negative charge on the carbon adjacent to the cyano group [ 76 77 ].…”
Section: Reviewmentioning
confidence: 99%
“…An addition–elimination mechanism has been previously proposed for the LiAlH 4 promoted decyanation of 2,2-diphenylpropionitrile and related nitriles. In such pathways, the phenyl groups probably favor the C–C bond cleavage by stabilizing the incipient negative charge on the carbon adjacent to the cyano group [ 76 77 ].…”
Section: Reviewmentioning
confidence: 99%
“…94 The solvents THF or HMPA favor the decyanation process in comparison with Et 2 O. We suggested that, in Et 2 O, the imine salt intermediate is stabilized by the cation Li + while in more basic and dissociative medium the C-C bond cleavage is favored.…”
Section: Scheme 14mentioning
confidence: 99%
“…Thus, the mechanism of decyanation of substrates other than α-aminonitriles induced by LiAlH 4 is not yet totally clarified. 94,97 Several pathways were proposed with organometallic reagents, a 4-centered transition state, an addition-elimination process or an electron transfer mechanism. Similarly, the decyanation induced in basic medium could proceed through an addition-elimination process or a sequence involving hydrolysis and decarboxylation.…”
Section: Photoinduced Decyanationsmentioning
confidence: 99%